Yarrowia lipolytica yeast use for the production of biomass and lipid - Delabio, Aline da Silva; Pires, Juliana Angelo; Harder, Márcia Nalesso Costa; Monteiro, Regina Teresa Rosim; Arthur, Valter (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2015)
Fuels from renewable energy are gaining space in a landscape where the unbridled use of fossil fuels endangers the world's energy future. Thus biofuels are possible substitutes for fossil fuels. The use of yeast in lipid synthesis is presented as an alternative since the lipids produced can serve as raw material for production of biodiesel. This study was conducted in order to assess the feasibility of production of lipid by Yarrowia lipolytica and a subsequent application as biodiesel. Yeasts of Yarrowia lipolytica were maintained in liquid medium, Yeast Extract Peptone Dextrose, and inoculated into medium containing agro-industrial waste (molasses and vinasse) and other available waste (urban runoff). After inoculation the medium was incubated without agitation for a period of 7; 14 and 21 days. Three bottles every seven days were taken for quantification of lipids. The length greater oil production occurred after 21 days of incubation, while greater biomass production occurred 14 days of incubation. The production of lipids was less than reported in the literature but production can be increased with the appropriate study of each nutrient composition of the culture medium. The study was conducted in laboratory scale values probably biomass and lipids are major industrial scale.